To Investigate the Branching Pattern of Segmental Branches of The Splenic Artery in Human Cadaveric Spleens Using the Dissection Technique - Devendra Kumar Sirohi (Asian Journal of Medical Research, 2017)
Background: The spleen, which is the primary lymphatic organ in the human body, receives its blood supply via the splenic artery, which is the primary branch of the celiac trunk. The structure traverses the lienorenal ligament and reaches the spleen hilum, where it bifurcates into 2-3 primary branches, each of which primarily divides into 2-4 subsidiary branches. Additionally, the inferior and superior polar arteries originate from the principal branches or splenic stem and enter the spleen pole directly without passing via the hilum. Aim: To investigate the branching pattern of segmental branches of the splenic artery in human cadaveric spleens using the dissection technique. Methodology: The current investigation involves the examination of 60 human cadaver spleens, without considering their age or sex. These spleens were preserved in a 10% formalin solution and were obtained from the Department of Anatomy, Venkateshwara IMS. The splenic artery was transected around 10 cm from the hilum of the spleen, followed by the removal of the spleen. The fascia and fat were removed at the hilum to reveal the segmental branches of the splenic artery. Initially, the main divisions of the splenic artery and any polar arteries were discovered and recorded. Subsequently, the length of these divisions and polar arteries was directly measured using a Digital Vernier Calliper. Results: Out of the 42 spleen samples, 70% had two major branches, 25% had three primary branches, and 5% had four primary branches. Out of the total samples, 15 (25%) exhibit superior polar arteries, 24 (40%) exhibit inferior polar arteries, and 3 (5%) exhibit both inferior and superior polar arteries. The superior PB had a range of lengths from 0.55 to 4.45 cm, with an average length of 1.69 cm and a median length of 1.31 cm. The average length of the middle PB varied between 0.41 and 2.18 cm, with an average length of 1.12 cm and a median length of 1.15 cm. The inferior PB exhibited a range of lengths between 0.34 and 5.36 cm, with an average length of 1.91 cm and a median length of 1.74 cm. The maximum diameter of the PB varied from 0.77 mm to 4.23 mm, with an average diameter of 2.31 mm and a median diameter of 2.36 mm. The middle PB exhibited a range of mean diameters from 0.77 mm to 3.74 mm, with an average diameter of 2.15 mm and a median diameter of 2.36 mm. The inferior diameter of the PB varied between 0.69 mm and 4.61 mm, with an average diameter of 2.19 mm and a median diameter of 2.09 mm. Conclusion: This research improves the existing knowledge about the morphometry of the segmental branches of the splenic artery, which is crucial for many spleen-sparing procedures that need accurate information about the spleen's vascular architecture.